Endoscopic Submucosal Dissection for the Treatment of Superficial Epithelial Gastric Neoplasia in a Portuguese Centre - Costa, RS (2019)
BACKGROUND: The emergence of endoscopic submucosal dissection (ESD) made possible en bloc resection of neoplastic gastric lesions, regardless of lesion size, with reduced rates of complications and recurrence. This technique has become the preferred method for curative resection, instead of conventional endoscopic mucosal resection and surgery, when distant metastases have negligible risk. In Western countries experience with this technique has evolved quickly, with an increasing number of case series reported in the literature. This study aims to report the short- and long-term outcomes of ESD in gastric epithelial neoplastic lesions by a single operator in a Portuguese centre. METHODS: A retrospective analysis of all gastric ESDs in a tertiary specialised unit during a 5-year period, between May 2012 and September 2017, was performed. RESULTS: A total of 114 ESDs of gastric epithelial lesions were performed during this period; 96.5% of them were removed en bloc and 87.6% with R0 resection. A curative treatment was achieved in 83.2% of the cases. Complications occurred in 13.2% of the procedures, including early and delayed bleeding in 12 patients (10.5%) and one perforation (0.9%). With a median follow-up period of 12 months (interquartile range [IQR] = 18), 6 cases of recurrence at the previous ESD site were diagnosed: 4 residual lesions and 2 local recurrences in previous R0 resections. Residual lesions occurred more often in patients with larger lesions (median = 40.0 mm, IQR = 26 vs. median = 20.0 mm, IQR = 15, p = 0.008) and with positive horizontal margins (HMs) after resection (50.0 vs. 0.0%, Fisher exact test, p < 0.001). The cumulative incidence of metachronous gastric lesions at 34 months was 16.1%. All new lesions were effectively treated using an endoscopic technique. The disease-specific survival at 12 months was 100%. CONCLUSION: This study showed that ESD is an effective resection technique for gastric lesions with a good safety profile, confirming other European series. Regardless, high en bloc resection positive HM is still a problem in some specimens resected by ESD. Endoscopic surveillance can detect local recurrence and new lesions during early stages, potentially treatable by endoscopy.